An evaluation of the experiences of guide dog owners visiting Scottish veterinary practices. (10th September 2016) - Fraser, M.; Girling, S. J.
Abstract : Guide dogs and their owners will visit a veterinary practice at least twice a year. The aim of this study was to evaluate what guide dog owners thought about these visits, in order to identify areas of good practice which could be incorporated into the undergraduate curriculum. Nine guide dog owners volunteered to take part in the study and were interviewed by the primary researcher. Thematic analysis was carried out and several themes were identified: good experiences were highlighted where staff had an understanding of visual impairment and the work of a guide dog; the importance of good communication skills involving the owner in the consultation; the need for veterinary professionals to understand the bond between an owner and guide dog; how medication and information could be provided in a user‐friendly format for someone affected by a visual impairment and concerns about costs and decision making for veterinary treatment. This work highlights the importance for veterinary staff to talk to, empathise with and understand the individual circumstances of their clients and identifies areas that should be included in veterinary education to better prepare students for the workplace.